Audited financial reporting and voluntary disclosure: International evidence on management earnings forecasts. Issue 2 (21st May 2018) - Liu, Rubing; Kong, Xiangting; San, Ziyao; Tsang, Albert
Abstract : In this paper, we extend prior research on the link between audited financial reporting and voluntary disclosure by examining international differences in the relationship between commitment to higher levels of audit verification of actual financial outcomes and management earnings forecasts (our proxy for voluntary disclosure), using firm‐level data from 30 non‐US countries. Our evidence that commitment to higher levels of audit verification (proxied by the choice of a Big 4 auditor, the amount of audit fees, and excess audit fees) is positively associated with the incidence and frequency of management forecasts, and with stock market reactions to such forecasts, supports the notion that audited financial reporting and voluntary disclosure of managers' private information are complements in countries around the world. We further find that the relation between audited financial reporting and management earnings forecasts is weaker for firms in countries with relatively stronger capital market development or with higher levels of investor protection, suggesting that audited financial reporting plays a more important complementary role in voluntary disclosure in countries with less‐developed institutions. Overall, our findings suggest that firm‐level commitment to better audited financial reporting and the strength of country‐level institutional characteristics play substitute roles in corporate voluntary disclosure decisions.